Vegetable seeds: A new perspective in future food development. Issue 11 (15th September 2022) - Roy, Sarita; Sarkar, Tanmay; Chakraborty, Runu
Abstract: Traditionally, vegetables are consumed as ingredients of daily household meals. Before cooking, vegetables are washed thoroughly, unpeeled, and deseeded, followed by chopping into desired shapes and sizes. Vegetable peels and seeds are also byproducts of various food industries. If they are not used, they will contribute significantly to global garbage. On the contrary, developing novel functional foods and food ingredients out of unorthodox sources has become a trending issue among researchers. The focus of this review was to access the utility of seed flour from 16 commonly eaten seed‐bearing vegetables such as ash gourd ( Benincasa hispida ), bitter gourd ( Momordica charantia ), bottle gourd ( Lagenaria siceraria ), buffalo gourd ( Cucurbita foetidissima ), capsicum ( Capsicum annuum ), drumstick ( Moringa oleifera ), Gnetum ( Gnetum gnemon ), hemp ( Cannabis sativa ), lady's finger ( Abelmoschus esculentus ), noni ( Morinda citrifolia ), pointed gourd ( Trichosanthes dioica ), pumpkin ( Cucurbita maxima ), ridge gourd ( Luffa acutangular ), snake gourd ( Trichosanthes cucumerina ), spine gourd ( Momordica dioica ), and tomato ( Solanum lycopersicum ) have been presented. A complete picture of the nutritional qualities, phytochemical constituents, health benefits of these vegetable seeds, and their impact on the fortification of ready‐to‐eat foods have been illustrated. The development of functional food goods (bakery products, milk products, cereal‐based products, and meat products) from food waste (vegetable seeds) is extensively discussed in this study. It also highlights possible research gaps related to this field. Novelty impact statement: Waste management is a key challenge to achieve the goal of sustainable development, particularly for the vegetable processing industries. Vegetable seeds contribute a hefty share in food waste generation and can be valorized as a food fortification and/or preservation agent.